Trends in hemolytic anemia-related mortality in the United States from 1999-2022 - Tuin, Ashley; Diehl, Tabitha; Billion, Taylor; Mirza, Mohsin; Tauseef, Abubakar; Abdul Jabbar, Ali Bin (Frontiers in Hematology, 2025)
BackgroundAnemia carries the third highest years lived with disability, and yet the subset of hemolytic anemia is associated with higher rates of mortality and complication than other types of anemia. There is a lack of data studying the more encompassing subset of hemolytic anemia mortality at a population level.MethodsIn this study, we analyzed the temporal trends of demographic and geographical differences in hemolytic anemia-related mortality in the United States from 1999-2022. Data was extruded from the CDC Wide-Ranging Online Data for Epidemiologic Research (WONDER) database. Crude mortality rates, age-adjusted mortality rates (AAMR), annual percent change (APC), and average annual percent change (AAPC) were determined with 95% confidence intervals (CIs) using the Joinpoint Regression Program.ResultsFrom 1999-2022, there were 46,924 deaths due to hemolytic anemia. Mortality rates decreased significantly from 1999–2016 before increasing significantly from 2016-2022. Mortality rates were higher in males, Black or African American people, and urban areas. Interestingly, all groups showed a similar increase in mortality rates in recent years except for people aged 15–24 years who showed consistently decreasing mortality over the study period.ConclusionHemolytic anemia-related mortality in the United States decreased overall between 1999 and 2022. While a decrease was seen between 1999 and 2016, an increase was seen starting from 2016, most prominently from 2019 to 2021 in most of the subgroups with males, African American and the south region having the worst AAMRs.